Comparison of perioperative automated versus manual two-dimensional tumor analysis in glioblastoma patients. Issue 95 (October 2017) - Kellner-Weldon, Frauke; Stippich, Christoph; Wiest, Roland; Lehmann, Vera; Meier, Raphael; Beck, Jürgen; Schucht, Philippe; Raabe, Andreas; Reyes, Mauricio; Bink, Andrea
Highlights: Comparison of human and automated detection of postoperative tumor in glioblastoma. Good agreement between automated and manual 2D annotations on preoperative data. Moderate interrater agreement for detection of postoperative residual tumor. Automated evaluation of postoperative tumor has trend towards overestimation. A pre-defined threshold could help overestimation due to misclassification. Abstract: Objectives: Current recommendations for the measurement of tumor size in glioblastoma continue to employ manually measured 2D product diameters of enhancing tumor. To overcome the rater dependent variability, this study aimed to evaluate the potential of automated 2D tumor analysis (ATA) compared to highly experienced rater teams in the workup of pre- and postoperative image interpretation in a routine clinical setting. Materials and methods: From 92 patients with newly diagnosed GB and performed surgery, manual rating of the sum product diameter (SPD) of enhancing tumor on magnetic resonance imaging (MRI) contrast enhanced T1w was compared to automated machine learning-based tumor analysis using FLAIR, T1w, T2w and contrast enhanced T1w. Results: Preoperative correlation of SPD between two rater teams (1 and 2) was r = 0.921 (p < 0.0001). Difference among the rater teams and ATA (p = 0.567) was not statistically significant. Correlation between team 1 vs. automated tumor analysis and team 2 vs. automated tumor analysis was r = 0.922 and r = 0.897, respectively (p < 0.0001 for both). For postoperative evaluation interrater agreement between team 1 and 2 was moderate (Kappa 0.53). Manual consensus classified 46 patients as completely resected enhancing tumor. Automated tumor analysis agreed in 13/46 (28%) due to overestimation caused by hemorrhage and choroid plexus enhancement. Conclusions: Automated 2D measurements can be promisingly translated into clinical trials in the preoperative evaluation. Immediate postoperative SPD evaluation for extent of resection is mainly influenced by postoperative blood depositions and poses challenges for human raters and ATA alike.